2021
DOI: 10.1080/2090598x.2021.1874628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the oncological outcomes of three different bacillus Calmette–Guérin strains in patients with high-grade T1 non-muscle-invasive bladder cancer

Abstract: Objective: : To determine whether there are significant differences in oncological outcomes between three different bacillus Calmette-Guérin (BCG) strains used for adjuvant intravesical immunotherapy in patients with high-grade T1 (T1HG) non-muscle-invasive bladder cancer (NMIBC). Patients and methods: : Data of 590 patients with a diagnosis of primary T1HG NMIBC were retrospectively reviewed. The study included 138 (23.4%) patients who were treated with the Moreau, 272 (46.1%) with the TICE, and 180 (30.5%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Data from these studies emphasize that response rates to BCG therapy were similar to those seen in primary tumors [ 63 , 73 , 74 , 75 ]. Interestingly, although not yet studied in post-CMT patients, various BCG strains were found to perform differently in high-risk NMIBC, with several studies showing the superiority of the BCG-TICE strain over RIVM [ 76 , 77 ]. Despite adequate BCG exposure, Weiss et al reported that 33% of patients had further NMIBC recurrences and 19% progressed to MIBC, respectively [ 75 ].…”
Section: Follow-up Regimen and Salvage Treatmentmentioning
confidence: 99%
“…Data from these studies emphasize that response rates to BCG therapy were similar to those seen in primary tumors [ 63 , 73 , 74 , 75 ]. Interestingly, although not yet studied in post-CMT patients, various BCG strains were found to perform differently in high-risk NMIBC, with several studies showing the superiority of the BCG-TICE strain over RIVM [ 76 , 77 ]. Despite adequate BCG exposure, Weiss et al reported that 33% of patients had further NMIBC recurrences and 19% progressed to MIBC, respectively [ 75 ].…”
Section: Follow-up Regimen and Salvage Treatmentmentioning
confidence: 99%
“…Sixty-two studies [ 2 , 3 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76...…”
Section: Resultsunclassified
“…The vast majority of the studies (n = 34, [ 24 , 25 , 26 , 27 , 28 , 29 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 48 , 50 , 51 , 53 , 55 , 56 , 60 , 62 , 63 , 65 , 68 , 69 , 71 , 75 , 76 , 77 , 79 , 80 , 81 ]) were single-arm with no direct comparison across other strains. On the contrary, the remaining n = 27 [ 2 , 3 , 23 , 30 , 31 , 32 , 33 , 43 , 44 , 45 , 47 , 49 , 52 , 54 , 57 , 58 , 59 , 61 , 64 , 66 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their original series, Krajewski et al [24] reported similar findings with the current analysis concerning both TICE and RIVM (5yr-RFS TICE : 61.1% and RFS RIVM : 60.5%). More interestingly, in a recently released multicentric comparative series of three strains (Moreau, TICE, and RIVM), Nowak et al were able to identify how RIVM strain was significantly associated with inferior RFS compared to the Moreau (hazard ratio [HR] 1.69 for RIVM; p = 0.034) and TICE (HR 1.87 for RIVM; p = 0.002) strains [25]; however, no significant differences in PFS were observed among any of the strains. D'Andrea et al [26] published a previous cohort study, which analyzed a retrospective head-to-head cohort of patients allocated to BCG TICE and Moreau, respectively.…”
Section: Discussionmentioning
confidence: 99%